When should probiotics be recommended? - Czerwionka-Szaflarska, Mieczysława; Romańczuk, Bartosz (Przewodnik Lekarza/Guide for GPs, 2009)
Probiotics are live microorganisms which when administered in adequate amounts confer a health benefit on a host. The most often used probiotic bacteria are lactic acid bacteria (Lactobacillus and Bifidobacterium) and Saccharomyces (Saccharomyces boulardii). The best known probiotic, whose activity has been examined in many clinical studies, is Lactobacillus rhamnosus GG (LGG). In this publication we present the results of different clinical studies concerning the use of probiotics in prevention and treatment of the chosen diseases, especially digestive tract pathologies.